2021
DOI: 10.1063/5.0064466
|View full text |Cite
|
Sign up to set email alerts
|

Large negative thermal quenching of yellow luminescence in non-polar InGaN/GaN quantum wells

Abstract: Large negative thermal quenching (NTQ) of the yellow luminescence (YL) for a temperature increase from 5 to 300 K is observed in nonpolar InGaN/GaN quantum well (QW) samples due to the thermal migration of carriers from the InGaN QW layers to the GaN barrier layers for the first time. Such an unusual phenomenon happens only when the carriers are optically excited inside the QW layers, providing solid evidence for the occurrence of thermal transfer of photoexcited carriers from the QW layers to the GaN barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Finally, we apply the analytic formulas to quantitatively reproduce Sshaped temperature dependence of PL peak positions in non-polar and semi-polar InGaN/GaN QWs micro-array samples. [8] Good agreement between theory and experiment is achieved so that the localization depths of 31.5 and 32.2 meV are determined for the non-and semi-polar QWs, respectively.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Finally, we apply the analytic formulas to quantitatively reproduce Sshaped temperature dependence of PL peak positions in non-polar and semi-polar InGaN/GaN QWs micro-array samples. [8] Good agreement between theory and experiment is achieved so that the localization depths of 31.5 and 32.2 meV are determined for the non-and semi-polar QWs, respectively.…”
mentioning
confidence: 62%
“…Variabletemperature photoluminescence (PL) spectroscopy is an important methodology for studying materials' luminescence mechanisms [5][6][7] and carrier dynamics. [8] For example, variable-temperature PL is frequently used to investigate temperature dependence of the fundamental bandgap of semiconductors, which usually monotonically shrinks with increasing the temperature. [9][10][11][12] Such shrinking behavior may be induced by both lattice dilatation and electron-phonon interactions, [13] which is described by several empirical formulas, such as Varshni's, [13] Pässler's, [14] and Bose-Einstein model formula.…”
mentioning
confidence: 99%
“…Recently, Zhao and his co-workers have investigated the roles of Si and C impurities in YL and BL of unintentionally and Si-doped GaN with different C and Si concentrations and suggested that C and Si impurities play an important role in linkage and competition of the blue and yellow luminescence . Very recently, several of the present authors have observed a substantial NTQ phenomenon in the YL in a sample with non- and semipolar InGaN/GaN quantum well microarrays grown on patterned GaN using a 370 nm laser excitation . The corresponding photon energy (∼3.351 eV) of the 370 nm laser is below the room-temperature bandgap (∼3.4 eV) of GaN but well above the effective bandgap of InGaN QWs.…”
Section: Introductionmentioning
confidence: 99%
“…28 Very recently, several of the present authors have observed a substantial NTQ phenomenon in the YL in a sample with non-and semipolar InGaN/GaN quantum well microarrays grown on patterned GaN using a 370 nm laser excitation. 29 The corresponding photon energy (∼3.351 eV) of the 370 nm laser is below the roomtemperature bandgap (∼3.4 eV) of GaN but well above the effective bandgap of InGaN QWs. It has been identified that the thermally enhanced transfer of photoexcited holes from the InGaN QWs to the GaN layer with increasing temperature is responsible for the observed considerable NTQ phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, suppressing or even reversing the thermal decline of solid luminescence, although a serious challenge, is highly desirable. Several different models have been proposed to interpret the TQ behavior of solid luminescence. But only in recent years has a large negative thermal quenching (NTQ) phenomenon been firmly demonstrated in the narrow-band red luminescence of Mn 4+ ions in fluoride phosphors of K 2 SiF 6 , K 2 TiF 6 , Rb 2 SiF 6 , etc., as well as in the broad-band yellow luminescence of deep acceptors in the wide bandgap semiconductor of GaN. , The discovery and demonstration of large NTQ in solid luminescence is of clearly both scientific and technological significance as well as broad interest. For instance, its photophysical mechanism is very interesting and could be very helpful for technologically solving the severe thermal degradation problem in phosphor-converted white LEDs which are the major devices in the state-of-the-art solid-state lighting revolution.…”
mentioning
confidence: 99%